2013
DOI: 10.1160/th13-04-0294
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation of autoantibodies: Insights into the mechanisms of immune thrombocytopenia

Abstract: Immune thrombocytopenia (ITP) is a bleeding disorder caused by IgG autoantibodies (AAbs) directed against platelets (PLTs). IgG effector functions depend on their Fc-constant region which undergoes posttranslational glycosylation. We investigated the role of Asn279-linked N-glycan of AAbs in vitro and in vivo. AAbs were purified from ITP patients (n=15) and N-glycans were enzymatically cleaved by endoglycosidase F. The effects of native AAbs and deglycosylated AAbs were compared in vitro on enhancement of phag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…For example, an IgG3 variant with hinge-region deletions that prevent binding to FCGR but not to FcRn was still transported across the human placenta [ 83 ]. Likewise, deglycosylated IgGs were transported in mice [ 84 ]. Furthermore, a comparison of glycosylation patterns between fetal and maternal IgG by Stapelton et al in 2018 concluded that IgG transport was not glycosylation selective [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, an IgG3 variant with hinge-region deletions that prevent binding to FCGR but not to FcRn was still transported across the human placenta [ 83 ]. Likewise, deglycosylated IgGs were transported in mice [ 84 ]. Furthermore, a comparison of glycosylation patterns between fetal and maternal IgG by Stapelton et al in 2018 concluded that IgG transport was not glycosylation selective [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…A NOD/SCID mouse model was used to investigate the elimination of human platelets by anti-GPV autoantibodies in ITP patients. 24 In brief, NOD/SCID mice (NOD.CB17-Prkdcscid/J; Stock No. complexes, 001303) were purchased from The Jackson Laboratory (Bar Harbor, ME, USA) via Charles River, Research Models and Services (Sulzfeld, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Pointing against involvement of FcγRs is the fact that an IgG3 variant with hinge-region deletions that prevents binding to all FcγR but retains FcRn binding was still transported to the fetus (154). Likewise, aglycosylated IgG variants that are unable to interact with FcγR, but bind FcRn, were transported in mice (155). Comparison of glycosylation patterns between fetal and maternal IgG showed that IgG transport was not glycosylation selective (143).…”
Section: Functional Consequence Of Fcrn Expression In Epitheliummentioning
confidence: 99%